On the Engagement of Excluded Groups in Inclusive Cities : Highlighting Good Practices and Key Challenges in the Global South - Mitlin, Diana Clare; Satterthwaite, David (World Bank, Washington, DC, 2016)
The term “inclusive cities” is increasingly being used as a “catch-all” phrase to signify intent but with little precision in its use. In this note we use “inclusive cities” to mean cities in which we see a commitment to an inclusive politics with the establishment of institutionalized interactions between organized groups of disadvantaged citizens and the state with local government taking a primary role. They are also cities in which governments have undertaken specific measures to secure improved access for low-income and otherwise disadvantaged groups to a range of essential goods and services including secure tenure for housing, inclusion in access to basic services and where required approval of and support for housing improvements. This note begins by considering who is excluded and from what and how. Seven challenges to the achievement of more inclusive cities are discussed: (i) lack of household income and the continuing prevalence of informal incomes; (ii) a lack of state investment capacity; (iii) a lack of political will; (iv) a lack of the basic data needed for identifying and addressing exclusion; (v) a lack of space for participation, especially by the lowest income groups; (vi) a lack of vision for what an inclusive city means within city government; and (vii) the constraints on inclusion from city governments organized sectorally. The note then discusses the metrics and indicators that can help inclusion and that have relevance for the post-2015 sustainable development agenda. These are challenges that governments and communities must tackle through their collective efforts. In terms of collaboration between groups, three particular challenges must be addressed:(i) to avoid being partial in their efforts and so to reach out to all groups in the city through finding forms of engagement that incentivize a breadth of activities drawing in all of those in need; (ii) to set up processes that outlive specific administrations or interests and that provide for continuity in collaboration between civil society and the state in each city; and (iii) to link across cities and city regions. We see a need to think about collaboration and joint efforts between city administration and surrounding municipalities, as well as a need to link experiences and efforts across cities. This should help in ensuring appropriate central government policies, regulatory frameworks, and the redistribution of resources.